Auditory‐visual integration modulates location‐specific repetition suppression of auditory responses. (28th July 2017) - Shrem, Talia; Murray, Micah M.; Deouell, Leon Y.
Abstract: Space is a dimension shared by different modalities, but at what stage spatial encoding is affected by multisensory processes is unclear. Early studies observed attenuation of N1/P2 auditory evoked responses following repetition of sounds from the same location. Here, we asked whether this effect is modulated by audiovisual interactions. In two experiments, using a repetition‐suppression paradigm, we presented pairs of tones in free field, where the test stimulus was a tone presented at a fixed lateral location. Experiment 1 established a neural index of auditory spatial sensitivity, by comparing the degree of attenuation of the response to test stimuli when they were preceded by an adapter sound at the same location versus 30° or 60° away. We found that the degree of attenuation at the P2 latency was inversely related to the spatial distance between the test stimulus and the adapter stimulus. In Experiment 2, the adapter stimulus was a tone presented from the same location or a more medial location than the test stimulus. The adapter stimulus was accompanied by a simultaneous flash displayed orthogonally from one of the two locations. Sound‐flash incongruence reduced accuracy in a same‐different location discrimination task (i.e., the ventriloquism effect) and reduced the location‐specific repetition‐suppression at the P2 latency. Importantly, this multisensory effect included topographic modulations, indicative of changes in the relative contribution of underlying sources across conditions. Our findings suggest that the auditory response at the P2 latency is affected by spatially selective brain activity, which is affected crossmodally by visual information.